In search of universal health coverage - highlighting the accessibility of health care to students with disabilities in Ghana: a qualitative study - Eric Abodey; Irene Vanderpuye; Isaac Mensah; Eric Badu (BMC, 2020)
Abstract Background Accessibility of health care to students with disabilities is a global concern. This is no less important in Ghana, however, to date, no study has been undertaken regarding access to health care to students with disabilities. This study, therefore, aims to explore the accessibility of health care to students with disabilities, in the quest of achieving universal health coverage in Ghana. Methods Qualitative methods, involving in-depth interviews were employed to collect data from 54 participants (29 students with disabilities, 17 health workers and 8 school mothers), selected through purposive sampling. Thematic analysis was used to analyze the data. Results The study identified three themes - accessibility, adequacy, and affordability. The study findings highlighted that universal health coverage for students with disabilities has not been achieved due to barriers in accessing health care. The barriers faced by students with disabilities were unfriendly physical environments, structures, equipment, limited support services and poor health insurance policy to finance health care. Conclusion The study concludes that the government should prioritize disability-related issues in health policy formulation, implementation and monitoring. The current provisions and requirements in the disability act should be prioritized, enforced and monitored to ensure adequate inclusion of disability issues in health services. Further, the current exemption policy under the National Health Insurance Scheme should be revised to adequately address the needs of people with disabilities.